PENGARUH KEBIASAAN BELAJAR TERHADAP KEPUASAN HASIL UJIAN PADA MATA KULIAH KONSEP KEBIDANAN - Yunik Windarti (Jurnal Ilmiah Kesehatan, 2016)
The effect of habitual learning towards satisfaction of the results of tests on the course concepts of midwifery. Factors influenced the results of tests from the satisfaction of learning activities that are done by the student itself. In fact, many of the students who learn only at certain times, especially during exams. This research aims to analyze the effect of habitual learning towards satisfaction of the results of tests on the course concepts of midwifery. Design of analytical research, the population of students of the Semester I Prodi D-III Kebidanan FKK UNUSA of 123 people, a large sample of 123 people, taken with a probability sampling technique with total sampling. Independent study habits variables, variable dependent satisfaction exam results. The data is analyzed using kruskal wallis test. The results showed almost entirely (78,9%) students had the habit of learning outcomes and is almost entirely (75,6%) students were declared not satisfied against the results of the test. The results of statistical tests obtained ρ = 0,023 < α = 0,05, H0 is rejected then it means there is a significant learning habits influence towards the satisfaction of the results tests on the course concepts of midwifery. The conclusion of this research study is not good habits will cause discontent against the examination results are obtained. For students is expected to change the habit of studying, focus more on the material obtained, multiply the reading, often visited the library, the science danmenimba from various media rather than just rely on from the material presented lecturer.